PENILAIAN EFISIENSI ENERGI GEDUNG IME UNSOED BERDASARKAN STANDAR BANGUNAN GEDUNG HIJAU (Jurnal Arsitektur ARCADE, 2026)
Global warming is the increase in Earth's average temperature, primarily driven by greenhouse gas (GHG) emissions. The building sector accounts for 39% of global carbon emissions, underscoring the urgent need for effective mitigation strategies. Implementing green building practices is critical for advancing resource efficiency and sustainable design. In Indonesia, Green Building regulations are regulated in the Minister of Public Works and Public Housing Regulation Number 21 of 2021, which stipulates seven assessment parameters. This study aims to assess the performance of energy-efficiency parameters in the Integrated Medical Education Building at Jenderal Soedirman University. The method used is a descriptive, quantitative analysis of planning documents, field observations, and technical calculations, including Overall Thermal Transfer Value (OTTV), Roof Thermal Transfer Value (RTTV), Window-to-Wall Ratio (WWR), Lighting Power Density (LPD), and utility system performance. The assessment results showed a score of 31 points out of a maximum of 46 points or 67.39%. Further evaluation showed that the building still requires technical recommendations to improve energy efficiency. The implementation of technical recommendations resulted in a significant increase in the achievement score, from 31 points (67.39%) to 45 points (97.56%).